Declining Atmospheric Sulfate Deposition in an Agricultural Watershed in Central Pennsylvania, USA. Issue 1 (1st November 2016) - Elkin, Kyle R.; Veith, Tamie L.; Lu, Haiming; Goslee, Sarah C.; Buda, Anthony R.; Collick, Amy S.; Folmar, Gordon J.; Kleinman, Peter J. A.; Bryant, Ray B.
Abstract : Core Ideas: Sulfate concentrations in an agriculturally dominated watershed respond to atmospheric deposition inputs. Rough budget estimates in the watershed suggest a depletion of the sulfur pool. Agricultural practices do not seem to mask effects of atmospheric deposition. Sulfur emissions in the northeastern United States are only 20% of levels measured in 1987 due to the enactment of the US federal Clean Air Act. While there are numerous reports of forested ecosystems recovering from acidification as a result of the decline in sulfur deposition, few studies describe such recovery in agricultural watersheds. We used long‐term (30+ yr) atmospheric and watershed data from a USDA experimental watershed to investigate whether daily agricultural practices masked the declining sulfur (as sulfate‐sulfur) trends seen in mainly forested watersheds. Over the study period, atmospheric wet deposition of sulfate‐sulfur decreased 75% while sulfate‐sulfur at the watershed decreased by approximately 30%. While the deposition of sulfur is detrimental to stream quality, the reduction of sulfur deposition in recent years has caused many soils in the watershed to develop sulfur deficiencies. Long‐term declines in watershed sulfur export reveal emerging concerns about reducing atmospheric sulfur levels.